Ethno-Medico-Botanical Studies On Katei Baba Sacred Grove And Nearby Area Of Adhalwadi From Akole Taluka, Ahmednagar District (Maharashtra) - C. K. WAGHCHAURE; S. S. NAIK; A. R. ABHANG (International Journal of Pharma and Bio Sciences, 2011)
Ethno-medico-botanical survey was conducted in the village, Adhalwadi and nearby area of Akole taluka in Ahmednagar district. In the study area Katei Baba, sacred grove was selected because of faith of the traditional healers. The area is rich in biodiversity. It was revealed that 20 medicinal plant species have been used for various remedies. The information collected from the traditional healers is rich and faithful source for traditional knowledge regarding medicinal plants.